A Review on Self Compacting Concrete with Cementitious Materials and Fibers - Memon, N. A.; Memon, M. A.; Lakho, N. A.; Memon, F. A.; Keerio, M. A.; Memon, A. N. (Engineering, Technology & Applied Science Research, 2018)
Self-compacted concrete (SCC) is cast in the formwork without compaction and it fulfills the formwork due to its own weight. SCC is considered to have many advantages in comparison with conventional concrete like improved construction quality, faster construction activity, reduced cost etc. SCC is produced with the same ingredients of normal concrete. However, cementitious materials are also adopted to replace the cement content in SCC in order to use waste materials from industries and agricultural products. To further enhance the performance of SCC, different types of fibers are tried in order to produce fiber reinforced SCC. The fibers in the concrete bridge the cracks and diffuse the crack propagation which improves mechanical properties. In developed countries SCC has reasonable acceptance in construction industry but in developing countries like Pakistan has not gained acceptance. This paper is focused on undertaking a review of SCC with cement replacement and fiber reinforcement materials. The main objective of this paper is to compile the literature in order to understand the various properties of SCC in fresh and hardened state when these cement replacement materials and fibers are used.